A new anchialine shrimp of the genus Procaris from Christmas Island: the first occurrence of the Procarididae in the Indian Ocean (Crustacea: Decapoda: Caridea) - Bruce, A. J.; Davie, P. J.f. (Zootaxa, 2006)
A fifth species of the anchialine shrimp genus Procaris is described from Christmas Island, northeast Indian Ocean. This marks the first record of the Procarididae from the Indian Ocean. The closest known congeneric species, and the only other known from the Indo-West Pacific region, is P. hawaiiana Holthuis, 1973, from Hawaii. The new species can be separated from other described species by its angular fifth abdominal pleuron, having the medial eye lobe longer than the lateral, and by having a distolateral tooth on the scaphocerite. A cladistic analysis suggests the new species is sister to the clade containing the Pacific, P. hawaiiana, and the Atlantic P. chacei.